Incidence and Interrelated Factors in Patients With Congenital Hypothyroidism as Detected by Newborn Screening in Guangxi, China. (19th January 2015) - Fan, Xin; Chen, Shaoke; Qian, Jiale; Sooranna, Suren; Luo, Jingi; Li, Chuan; Tang, Qin; Lin, Caijuan
Background . A newborn screening program (NSP) for congenital hypothyroidism (CH) was carried out in Guangxi in order to understand the incidence of CH and the factors interrelated to major types of CH in this region of China. Methods . During 2009 to 2013, data from 930 612 newborns attending NSP in Guangxi were collected. Patients were classified with either permanent CH (PCH) or transient CH (TCH) after 2 years of progressive study. Results . A total of 1210 patients were confirmed with CH with an incidence of 1/769, including 68 PCH and 126 TCH cases with incidences of 1/6673 and 1/3385, respectively. The frequency of thyroid stimulating hormone values greater than 5 mIU/L was 7.2%, which, based on WHO guidelines, suggests that the population was mildly iodine deficient. Conclusions . The incidence of CH was high in Guangxi. Approximately two thirds of CH patients were TCH, which may be due to a deficiency in iodine within the population.